An Economic Analysis of Credit Availment for Grape Cultivation and Value Addition from Different Sources in Vijayapura District of Karnataka, India - , Asha Biradar, Prabhuling Tevari, G B Lokesh, Devendra Beeraladinni, Shivanand Kammar (Archives of Current Research International, 2024)
The present study aims to analyze the extent of credit availment from different sources for grape cultivation and value addition in Vijayapura district, which is having the highest area under grape cultivation in Karnataka state. As the grape requires high maintenance expenses, its economic analysis is of great importance in its present status. The primary data was collected from 90 respondent grape farmers in the study area. The finding of the study revealed that the majority of the sample farmers (40%) have availed of short-term credit from commercial banks, followed by RRBs (36.66%), and cooperative banks/societies (23.34%) for grape cultivation. In contrast, for raisin-making activities, only 35 respondent farmers have availed themselves of additional non-institutional sources of credit, and the other 55 sample farmers were self-funding. Among the non-institutional sources, 57.15 per cent of the sample farmers borrowed loans from friends and relatives, while 42.85 per cent used moneylenders as a source of non-institutional credit for raisin-making purposes. All the sample farmers in the study area borrowed an average of ₹ 1,46,883 per acre from institutional sources for grape cultivation and the overall recovery rate for institutional sources was 83.81 per cent. The average amount of credit borrowed from moneylenders and friends or relatives by the sample farmers in the study area was ₹ 1,67,372 and the recovery rate was 59.32 per cent. The results indicated that the majority of farmers taking a loan from institutional sources for grape cultivation and for the raisin-making again obtained loans from non-institutional sources despite the higher interest rates since the credit quantity obtained from institutional sources was insufficient for both grape production and value addition (raisin making). To encourage this type of small-scale industry in rural areas, the government should devise special programmes that encourage farmers to engage in value-added activities.